Linking Ambidextrous Organizational Culture to Innovative Behavior: A Moderated Mediation Model of Psychological Empowerment and Transformational Leadership - Liu, Yanbin; Wang, Wei; Chen, Dusheng (Frontiers in Psychology, 2019)
Research into innovative behavior is not new, but its importance for organizational effectiveness has become even more evident in recent years. However, the psychological processes and underlying mechanism concerning how and why innovative behavior occurs within an organization still invite more investigation. The present study considers ambidextrous organizational culture as a pro-innovation culture and proposes that it can be perceived by employees, which leads to their innovative behavior. This study adds clarity by exploring the impact of perceived ambidextrous organizational culture on employees’ reactions related to innovation via the intermediate mechanism of psychological empowerment and the moderating condition of transformational leadership. Hypotheses are derived from a motivational perspective based on self-determination theory. Results are based on data collected from 647 Chinese employee-supervisor dyads. This study finds that employees’ perceptions of ambidextrous organizational culture have an indirect effect on innovative behavior through psychological empowerment. Specifically, the positive indirect relationship is amplified when transformational leadership is at a higher level. Our findings show how the mediating mechanism of psychological empowerment and the moderating condition of transformational leadership work together to improve innovation by individuals. The findings reveal several ways in which organizations can strategically focus on their cultural and supervisory training, such as applying this model to improve employees’ outcome related to innovation.